Indoor Disaster Detection and Real-Time Escape Guidance System - Noh, Dae-Yeon; Park, Yoon-Young; Jung, Kang-Hee; Lee, Ho-Won; Kye, Joong-Eup (International Journal of Engineering and Technology, 2026)
Background/Objectives: When disasters occur in crowded indoor spaces, many property and human lives are lost. Simulate an indoor disaster escape system to minimize damage.Methods/Statistical analysis: Data measured by sensors or disaster robots are sent to middleware responsible for the area. Each middleware uses data to determine whether a disaster has occurred indoors. If a disaster occurs, locate victims of disaster and provide safe escape routes through pre-built maps. Through these methods, we simulate whether a disaster occurred and how well we can identify the escape route.Findings: BLE BEACON was used to locate victims of disaster. Later, he informed the victim of the shortest route to escape through middleware and servers. As a result, they were able to create indoor navigation with errors of about 3 meters. Using this system, it was confirmed that it could escape indoors.Improvements/Applications: The indoor disaster detection and escape route guidance system provides information on the existence of an indoor disaster. And the victim can identify safe escape routes.
Keywords: Disaster; Indoor; Escape; Simulation; Detection.